PENGARUH ORIENTASI KEWIRAUSAHAAN DAN INOVASI PRODUK TERHADAP KINERJA UMKM BATIK GEDOG KHAS TUBAN - Miftakhul Jannah; Anugrahini Irawati; Hadi Purnomo (Eco-Entrepreneur, 2019)
There’re so many factors that effect on business performance at of typicalgedog batik SMEs in Tuban. This can be in the in the form of entrepreneurialorientation factor and product innovation. The aims of this research are (a) todetermine whether the Entrepreneurship orientation variable effect on variableperformance of typical gedog batik SMEs in Tuban. (b) to determine whetherproduct innovation variable effects on variable performance of of typical gedogbatik SMEs in Tuban. (c) to determine whether the Entrepreneurship orientationand Product Innovation variable simultaneously effect on variable performance oftypical gedog batik SMEs in Tuban. This research used the population as much as 47 entrepreneur of typical batik in Tuban as samples. The method used is multiplelinear regression analysis. Using this analysis, the results indicate that 1) the entrepreurship orientationvariable has positive and significant effect on variable performance of typical gedogbatik SMEs in Tuban. 2) product innovation variable has positive and significanteffect on variable performance of typical gedog batik SMEs in Tuban. 3)simultaneously, the entrepreneurship orientation and product innovation variableseffect on variable performance of typical gedog batik SMEs in Tuban. 4)entrepreneurship orientation variable is the dominant effect on variableperformance of typical gedog batik SMEs in Tuban.